2021
DOI: 10.1038/s41541-021-00342-3
|View full text |Cite
|
Sign up to set email alerts
|

A conditionally replication-defective cytomegalovirus vaccine elicits potent and diverse functional monoclonal antibodies in a phase I clinical trial

Abstract: A conditionally replication-defective human cytomegalovirus (HCMV) vaccine, V160, was shown to be safe and immunogenic in a two-part, double-blind, randomized, placebo-controlled phase I clinical trial (NCT01986010). However, the specificities and functional properties of V160-elicited antibodies remain undefined. Here, we characterized 272 monoclonal antibodies (mAbs) isolated from single memory B cells of six V160-vaccinated subjects. The mAbs bind to diverse HCMV antigens, including multiple components of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…It has been suggested that Fc-mediated effector functions of antibodies are critical for the observed efficacy ( 69 ). Complement-enhanced neutralization was detected in the sera from people who received a gB vaccine, suggesting that complement may be one of the protective mechanisms ( 68 , 70 ). Notably, ORF4 has been demonstrated to be a virulence factor in the MHV-68 model during acute replication, but it is not necessary for latency establishment ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Fc-mediated effector functions of antibodies are critical for the observed efficacy ( 69 ). Complement-enhanced neutralization was detected in the sera from people who received a gB vaccine, suggesting that complement may be one of the protective mechanisms ( 68 , 70 ). Notably, ORF4 has been demonstrated to be a virulence factor in the MHV-68 model during acute replication, but it is not necessary for latency establishment ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is evidence that there is a unique epitope that is presented on cellassociated gB, but not on soluble gB. Antibody 13-929 was identified in the original binding to whole virion screen but removed from the Li et al paper 23 after they did not find a specific glycoprotein complex that this antibody bound to. Since 13% of the virion-binding mAbs isolated were gB-specific, cell-associated gB binding could be used to screen for functional gB-specific mAbs within the B cell repertoire of vaccinated or naturally infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Human serum samples were reported before 21 . Rabbit, mouse, guinea pig and cotton rat serum samples were taken from animals housed in the animal facility in the research laboratories at Merck & Co., Inc., West Point, PA, USA.…”
Section: Methodsmentioning
confidence: 99%